An overview on the freshwater sponge fauna (Demospongiae: Spongillida) of New Zealand and New Caledonia with new insights into Heterorotula from deep thermal vents of the Lake Taupo. Issue 35 (25th September 2019) - Pronzato, Roberto; Manconi, Renata
ABSTRACT: Data on the freshwater sponge fauna of New Caledonia and New Zealand (5 species, 3 genera, and 2 families) of the order Spongillida (Porifera, Demospongiae) is reported in the framework of an assessment of Australasian biodiversity. Literature screening and a comparative study by LM and SEM of these poorly known taxa on the basis of historical and recent materials delineated the compositions of local spongillofauna. Pachyrotula raceki, Oncosclera diahoti and Heterorotula caledonensis are endemic to New Caledonia, as is the monospecific genus Pachyrotula . New Caledonia shares Heterorotula multidentata with Eastern Australia. The endemic Heterorotula kakahuensis is known from New Zealand. Results highlighted (a) the problematic status of Oncosclera diahoti ; (b) the congeneric divergence/convergence of traits among closely related genera, i.e. Heterorotula and Ephydatia, and yielded (c) the discovery in BMNH material of a New Zealand Spongillida, sharing some morphotraits with the genus Pottsiela never recorded before in Australasia. Further integrated molecular, morphological and biogeographical analyses will clarify the tangled phylogenetic and evolutionary history of Australasian and Gondwanan lineages of Spongillida.